Buddhism in Central Asia - Meinert, Carmen,; Sorensen, Henrik Hjort, (Dynamics in the History of Religions;, 2020)
"The ERC-funded research project BuddhistRoad aims to create a new framework to enable understanding of the complexities in the dynamics of cultural encounter and religious transfer in pre-modern Eastern Central Asia. Buddhism was one major factor in this exchange: for the first time the multi-layered relationships between the trans-regional Buddhist traditions (Chinese, Indian, Tibetan) and those based on local Buddhist cultures (Khotanese, Uyghur, Tangut, Khitan) will be explored in a systematic way. The first volume Buddhism in Central Asia (Part I): Patronage, Legitimation, Sacred Space, and Pilgrimage is based on the start-up conference held on May 23rd-25th, 2018, at CERES, Ruhr-Universität Bochum (Germany) and focuses on the first two of altogether six thematic topics to be dealt with in the project, namely on "patronage and legitimation strategy" as well as "sacred space and pilgrimage."".